Profesionalisme Guru: Antara Beban dan Tanggung Jawab - M. Asep Fathur Rozi (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2015)
In the learning process, one who affects student learning achievements was a teacher, because the teacher is a component who cannot be released in education sector. The ideal teacher can received by each related parties. From the perspective of students, the ideal teachers are teachers who having the appearance in such a way, as a source of motivation, and fun learning.